Isothermal Remodelling of the Biosorption of Congo Red onto Kaolin (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2023)
A remodeling analysis was conducted on the sorption isotherm data for Congo Red adsorption onto kaolin using nonlinear regression. (CR)  also known as 1-naphthalenesulfonic acid, 3,3′-(4,4′-biphenylenebis(azo)) bis(4-amino-) disodium salt, is a synthetic anionic azo dye widely utilized in various industrial sectors, including rubber, plastic, textiles, paper, and printing. This dye is of significant interest due to its versatile applications and unique chemical properties. To prevent overfitting due to the limited data points, isotherm models with up to three parameters were utilized. Statistical analysis based on error function assessments, including root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), accuracy factor (AF), bias factor (BF), Bayesian Information Criterion (BIC), corrected AICc (Akaike Information Criterion), and Hannan-Quinn Criterion (HQC), revealed that the best performance was achieved by the Freundlich model, followed by the Langmuir and Jovanovic models, which ranked as the top three models.The best isotherm model was found to be the Unilan followed by (descending order) Brouers–Sotolongo, Hill, Sips and Langmuir. The Unilan maximum adsorption capacity, shows large deviation from the experimentally observed value with a large 95% confidence interval, indicating poor fitting parameters despite being the best model based on the error function analysis. The next best model was Brouers–Sotolongo with a maximum adsorption capacity, qmBS of 5.48 mg g-1 (95% confidence interval from 4.791 to 6.172) which agrees with experimental observations. The value of the maximum monolayer adsorption capacity for Congo Red binding to kaolin according to the Langmuir’s parameter  qmL was 5.49 mg g-1 (95% Confidence interval from 5.018 to 5.967), while bL (L mg-1), the Langmuir model constants was 0.5 L mg-1 (95% C.I. from 0.285 to 0.710).
Keywords: Congo Red; Adsorption; Kaolinite; Freundlich; Langmuir